Comparison of Financial Performance with Financial Ratio Analysis of Telecommunication Services Companies Listed on the Indonesian Stock Exchange 2019-2022 - Anita Felisia Irwanto; A An Arief Jusuf (PT FORMOSA CENDEKIA GLOBAL, 2023)
The research was conducted to determine the comparison of financial performance with financial ratio analysis. The population of telecommunication service companies listed on the IDX 2019-2022 is 13 companies. And the company sample is 8 companies. Descriptive quantitative method. The research results of the Telecommunications Services Company are in good condition in terms of liquidity ratios. The financial performance of solvency in good condition from debt to asset ratio and debt to equity ratio is PT Lck Global Kedaton. Receivables Turnover and Total Assets Turnover are PT Smartfren Telecom Tbk and PT Jasnita Telekomindo Tbk in good condition in terms of activity. Profitability, seen from net profit margin, return on assets and return on equity, is that PT Telkom Indonesia is in good condition.